A case of aceruloplasminaemia: abnormal serum ceruloplasmin protein without ferroxidase activity. Issue 4 (1st April 2002) - Takeuchi, Y; Yoshikawa, M; Tsujino, T; Kohno, S; Tsukamoto, N; Shiroi, A; Kikuchi, E; Fukui, H; Miyajima, H
Abstract : A 34 year old diabetic man with a complete deficiency of serum ferroxidase activity, regardless of the presence of serum ceruloplasmin (Cp), a multicopper ferroxidase protein, is described. The patient had had diabetes mellitus for 13 years, and was also found to have retinal degeneration accompanied by the development of a hearing disturbance of unknown aetiology. Laboratory examination showed markedly increased serum ferritin and low serum iron. Magnetic resonance imaging showed a pronounced hypointensity in the putamen, caudate, cerebellar dentate, and thalamus on T2 weighted images, and also disclosed a low level signal in the liver, suggesting the accumulation of some magnetic substances in the brain and liver. Liver biopsies histochemically identified iron deposition in the hepatocytes. Most of these findings were consistent with the newly established autosomal recessive disease "aceruloplasminaemia", except for the presence of serum Cp and the lack of apparent neurological symptoms. Interestingly, no ferroxidase activity was detected in the patient's serum, whereas suppressed ferroxidase activity was found in his mother's serum. A nucleotide sequence analysis of the Cp gene showed two mutations; a C to T substitution at nucleotide 2701 in exon 16, resulting in a nonsense mutation at amino acid 882 (Arg882ter), and a T to G substitution at nucleotide 2991 in exon 17, resulting in an amino acid alternation at amino acid 978 (His978Gln). The second mutation was also found in the patient's mother. The absence of serum ferroxidase activity despite the presence of serum Cp protein in this compound heterozygote was considered to be due to the production of a non-functional Cp harbouring no ferroxidase activity.